Tolling motorways in the time of economic downturn: the case of Portugal - Amorim, Marco; Lobo, António; Couto, António (Transport, 2019)
The recent European debt crisis has led many governments to impose strict measures to alleviate public expenditure and increase revenue, especially in the southern countries. Many public services and infrastructures became more costly for users due to the increase of existing fees or the implementation of new ones. In Portugal, one of the measures adopted by the government consisted in the removal of shadow tolls and the application of the user-pays principle to the entire network of rural motorways. To rapidly implement, this measure, in the context of financial constraints, the Electronic Toll Collection (ETC), materialized by the installation of gantries in selected motorway segments, was the preferred solution over the more time and resource consuming construction of toll plazas. Toll revenue is directly collected by the state, which intends to cover, at least partially, the expenses associated with the contractual payments to private concessionaires for the traffic using these roads. The main objective of this research is to provide a new optimization tool to allocate toll gantries to the segments of an existing motorway with the aim of maximizing toll revenue, based on the case study of Portuguese motorways. A macroscopic decision model that predicts drivers’ decision on using a tolled segment or the fastest alternative route and an optimization model that sets the price and location of toll gantries along a given motorway work together to provide a valuable tool to maximize the revenue. A special focus has been placed on scenarios of economic downturn, characterized by a negative growth of the Gross Domestic Product (GDP); however, the new tool allows making explanatory analyses for situations of economic growth. The results show that the optimal configuration for ETC vary with the macroeconomic scenario, with the number of tolled segments and price per kilometre inducing relevant variations on the revenue and traffic volume. The proposed methodology may be applied in other countries to assist decision makers in the implementation of ETC in motorways under different conditions. The required data is easy to collect from sources at the disposal of the practitioners.